Molecular markers of recurrence of basal cell skin cancer - Rifat R. Saytburkhanov; Alexey A. Kubanov; Irina N. Kondrakhina; Xenia I. Plakhova (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
Basal cell carcinoma is the most common malignant neoplasm, andits incidence has been rapidly increasing worldwide. This malignancy is a serious public health problem that can lead to disability and severe aesthetic damage. The results of the analysis of gene expression and proteomic profiling of tumor cells and the tumor microenvironment indicate that certain molecules involved in the pathogenetic pathways of basal cell skin cancer may represent new prognostic biomarkers or serve as the basis for their development. The purpose of this review is to summarize information on known genes, proteins, and enzymes that can be used to diagnose, monitor therapy, and predict the course of basal cell skin cancer. The PubMed, MedLine, Web of Science and RSCI databases were used to search for the necessary literature.